NATURALNE I SPOŁECZNE PRAWA CZŁOWIEKA W NAUCZANIU PAPIEŻA LEONA XIII - Sadowski, Mirosław (Zeszyty Prawnicze, 2016)
THE NATURAL AND SOCIAL HUMAN RIGHTS IN THE POPE LEON XIII’S TEACHING Summary The aim of this paper is to show that the category of human rights, one of the fundamentals of the modern political debate, was present in the pope’s social teaching since its beginning, namely since the pontificate of Leon XIII (1878 – 1903). A comparison between the pope’s views and the liberal doctrine of human rights indicates that both in the pope’s teaching and in the liberal conceptions, not only the subject of those rights but also their object are repeatedly identical. Their origin though is undoubtedly different. For the liberals the source of human rights are the social convention and the positive law. For Leon XIII the fundamental of human rights is the conviction that human being as imago Dei possesses an inalienable dignity which constitutes the foundation and the source of his rights. The second source of human rights in the pope’s teaching is the natural law. Leon XIII considered the right to possess private property to be the most important of human rights. The conception of natural and social human rights developed by him was a turning point in the social teaching of the Catholic Church, and moreover it was Leon XIII who presented it for the first time.